Recurrence Rate of Abdominal Tuberculosis in Cases Presenting With Acute Abdomen - Sidra Aleem, Naeem Sarwar, Sajida Naseem, Muhammad Arshad Abbas, Sohail Hameed, Rafay Bukhari (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acute abdomen is considered as one of the major causes leading to surgical emergencies and intestinal obstruction, perforation and many other underlying causes resulting in surgical consultation. Aim: To determine rate of recurrence of abd. TB in cases presenting with acute abdomen to Sh. Zayed Hospital, Rahim Yar Khan. Study Design: The Cross sectional study Sampling Technique: Consecutive sampling non probability Sampling Technique Methods: This particular study was conducted at teaching hospital Rahim Yar Khan from 10-04-2021 to 31-12-2022 in which the cases of both genders with age ranging from 15 to 60 years having acute abdomen presenting within 24 hours were included. Abdominal tuberculosis (TB) was labeled on histopathology when there was caseating granuloma. Results: There were around 90 cases included in this present study. Out of these 50 (55.55%) were male patients and the rest of 40 (44.44%) were female patients. Approximately 34.91±11.35 was the Mean age in years of the patients and 67.13±21.39 in Kilograms was the mean weight. There were about 22 (24.44%) cases which had previous history of abdominal surgery. The abdominal tuberculosis was diagnosed in 30 (33.33%) of the cases as shown in figure 12. Abdominal TB was observed in 16 (32%) males and 14 (35%) females in their respective groups with p= 0.81. TB was detected in 20 (35.71%) out of 56 cases in age group 15 to 39 years as compared to 6 (25%) out of 24 cases with age 40-60 years with p= 0.44. There was no significant difference in terms of abdominal TB and weight (p= 1.0) and also with cases that had previous surgery with p= 0.57. Conclusion: The abdominal tuberculosis (TB) is detected in one third of all the cases presenting with acute abdomen and there is no significant association of this with any of the confounding variable of the study.